2021
DOI: 10.1039/d0sc05328g
|View full text |Cite
|
Sign up to set email alerts
|

In vivo oral insulin delivery via covalent organic frameworks

Abstract: We report the successful use of a gastro-resistant covalent organic framework for in vivo oral delivery of insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 98 publications
1
47
0
Order By: Relevance
“…Recently, Benyettou et al reported imine-linked COF nanoparticles that can be used for efficient in vivo oral insulin delivery. 240 Using a seeded growth method, 210,241,242 they prepared an imine-linked nCOF by condensing 2,6-diformylpyridine (DFP) with 4,4′,4′′-(1,3,5-triazine-2,4,6-triyl)trianiline (TTA) (denoted as TTA-DFP-nCOF 153 ), as shown in Fig. 11a.…”
Section: Biomedical Applications Of Popsmentioning
confidence: 99%
“…Recently, Benyettou et al reported imine-linked COF nanoparticles that can be used for efficient in vivo oral insulin delivery. 240 Using a seeded growth method, 210,241,242 they prepared an imine-linked nCOF by condensing 2,6-diformylpyridine (DFP) with 4,4′,4′′-(1,3,5-triazine-2,4,6-triyl)trianiline (TTA) (denoted as TTA-DFP-nCOF 153 ), as shown in Fig. 11a.…”
Section: Biomedical Applications Of Popsmentioning
confidence: 99%
“…High dose of oral PA is often associated with nausea, vomiting and diarrhoea. Most importantly, developments of oral PA delivery have been seriously hindered by the gastrointestinal (GI) tract challenge [ 4 ]. PA via individual oral is generally degraded under the harsh gastric environments thereby limiting its transport across the intestinal epithelium into the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages of MOFs have led to various applications including lithium-ion batteries, gas-vapor separation, gas storage, and catalysis (23)(24)(25). The MOF abilities, particularly its excellent trapping and releasing molecules of interest, are extremely advantageous for biological studies (26)(27)(28). Specifically, several essential biomolecules, including bulk metals (e.g., potassium, calcium, and magnesium), trace metals (e.g., zinc, iron, and manganese), amino acids, neurotransmitters, and even vitamins, can be stored and constantly released from the MOFs over a long period of time (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…The MOF abilities, particularly its excellent trapping and releasing molecules of interest, are extremely advantageous for biological studies (26)(27)(28). Specifically, several essential biomolecules, including bulk metals (e.g., potassium, calcium, and magnesium), trace metals (e.g., zinc, iron, and manganese), amino acids, neurotransmitters, and even vitamins, can be stored and constantly released from the MOFs over a long period of time (28)(29)(30)(31)(32). Therefore, such biomolecule-embedded MOFs can be extremely useful for controlling stem cell fates, which partially replace the role of the surrounding 3D cellular microenvironment in vivo.…”
Section: Introductionmentioning
confidence: 99%